The Effects of Storage on Red Blood Cell Acidity, Hemolysis, Methemoglobin level and Osmotic Fragility - Sirirat, Tanasan; Chulsomlee, Sucha; Sanmun, Duangmanee; Tangrua, Nonthaya; Sirirat, Kanjana (Journal of Health Sciences and Wellness, 2025)
Red blood cells play a crucial role in transporting oxygen to various tissues and organs of the body. During storage, changes occur within red blood cells. This experimental laboratory research aimed to study the acidity using a pH meter, hemolysis by measuring absorbance at 540 nm, methemoglobin level by measuring absorbance at 500 and 630 nm, and red blood cells fragility using the osmotic fragility test with CPDA-1 as anticoagulant. Samples were collected in CPDA-1 anticoagulant tubes from 30 healthy volunteers aged between 20 and 45 years, with no underlying health conditions. All samples were stored at 4 °C and analyzed on days 7, 14, and 21. Data were analyzed using one-way ANOVA. The results showed that on the 7th day, there was a decrease in acidity levels and a statistically significant increase in osmotic fragility on day 7 (p- value < 0.01). Additionally, free hemoglobin and methemoglobin levels showed statistically significant increases on day 14 with p-values of 0.02 and 0.0, respectively. In conclusion, red blood cells stored with CPDA-1 exhibit changes in acidity, hemolysis, methemoglobin levels, and osmotic fragility. These findings provide valuable supplementary information for consideration when selecting appropriate packed red blood cell for transfusion. Moreover, the study contributes to a better understanding of red blood cell membrane stability and oxidative damage during storage, which may be relevant for hematological research and the development of improved preservation techniques in clinical laboratory practice.